2003
DOI: 10.1023/b:agen.0000011800.04507.4b
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of angiogenic initiation and disruption of newly established human vascular networks by juice from Morinda citrifolia (noni)

Abstract: noni, the juice of the fruit from the Morinda citrifolia plant, has been used for centuries as a medicinal agent. We tested the effects of noni juice in a three-dimensional fibrin clot matrix model using human placental vein and human breast tumor explants as sources for angiogenic vessel development. Noni in concentrations of 5% (vol/vol) or greater was highly effective in inhibiting the initiation of new vessel sprouts from placental vein explants, compared with initiation in control explants in media supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 18 publications
3
49
0
1
Order By: Relevance
“…Twenty thousand or 4x10 4 DCs were co-cultured with 2x10 5 splenocytes, B, CD4 + T, CD8 + T, or NK cells in a final volume of 100 μl RPMI-1640 culture medium in 96-well round bottom plates for 3 to 8 days. Sixteen hours before the end of culture, 1 μCi [methyl-…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty thousand or 4x10 4 DCs were co-cultured with 2x10 5 splenocytes, B, CD4 + T, CD8 + T, or NK cells in a final volume of 100 μl RPMI-1640 culture medium in 96-well round bottom plates for 3 to 8 days. Sixteen hours before the end of culture, 1 μCi [methyl-…”
Section: Methodsmentioning
confidence: 99%
“…Two hundred thousand B cells were added into the insert, whilst 4x10 4 DCs were added either into the insert (co-culture) or into the well (culture separately). On day 3, 1 μCi [methyl-…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus Noni juice inhibit the growth and mutations of malignant cells and induce programmed cell death or apoptosis. 28 Polysaccharides Glucoronic acid, galactose, arabinose, rhamnose, glycosides and trisaccharide fatty acid ester showed immuno-stimulatory, immune-modulatory, antibacterial, antitumor and anticancer activity. 29 6-D-Glucopyranose pentaacetate is sulphated polysaccharides, which undermine the interaction between glucosaminoglycan and certain proteins.…”
Section: Epigallocatechin Gallate (Egcg)mentioning
confidence: 99%
“…They also found that 10% Noni juice in media was an effective inhibitor of capillary initiation in explants from human breast tumors. 28 Chemoprotective effect Evaluate the chemoprotective effect of ethanolic extract of M. citrifolia (EEMC) fruits by simultaneous administration orally at the dose of 100 and 200 mg/kg b.wt. in rats.…”
Section: Effect On Colorectal Cancermentioning
confidence: 99%